Jungermannenone A and B induce ROS- and cell cycle-dependent apoptosis in prostate cancer cells in vitro - Guo Yan-xia; Lin Zhao-min; Wang Mei-juan; Dong Yi-wen; Niu Huan-min; Young Charles YF; Lou Hong-xiang; Yuan Hui-qing (Acta Pharmacologica Sinica, 2017)
Aim: Jungermannenone A and B (JA, JB) are new ent-kaurane diterpenoids isolated from Chinese liverwort Jungermannia fauriana, which show anti-proliferation activities in cancer cells. In this study we investigated the mechanisms underlying the anticancer action of JA and JB in PC3 human prostate cancer cells in vitro. Methods: A panel of 9 human cancer cell lines was tested. Cell proliferation was assessed with a real-time cell analyzer and MTT assay. Cell apoptosis, cell cycle distribution and ROS levels were measured using cytometry. Mitochondrial damage was examined by transmission electron microscopy. DNA damage was detected with comet assay. Apoptotic, DNA damage- and cell cycle-related proteins were analyzed using Western blotting. The expression of DNA repair genes was measured with qRT-PCR. Results: Both JA and JB exerted potent anti-proliferative action against the 9 cancer cell lines, and PC3 cells were more sensitive with IC50 values of 1.34±0.09 and 4.93±0.20 μmol/L, respectively. JA (1.5 μmol/L) and JB (5 μmol/L) induced PC3 cell apoptosis, which was attenuated by the caspase inhibitor Z-VAD. Furthermore, both JA and JB caused mitochondrial damage and ROS accumulation in PC3 cells, whereas vitamin C blocked the ROS accumulation and attenuated the cytotoxicity of JA and JB. Moreover, both JA and JB induced DNA damage, accompanied by downregulated DNA repair proteins Ku70/Ku80 and RDA51. JA induced marked cell cycle arrest at the G0/G1 phase, which was related to c-Myc suppression, whereas JB enforced the cell cycle blockade in the G2/M phase, which associated with activation of the JNK signaling. Conclusion: Both JA and JB induce prostate cancer apoptosis via ROS accumulation and induction of cell cycle arrest.